Optimization of calcium-based bioclogging and biocementation of sand - Chu, Jian (2016)
Bioclogging and biocementation can be used to improve the geotechnical properties of sand. These processes can be performed by adsorption of urease-producing bacterial cells on the sand grain surfaces, which is followed by crystallization of calcite produced from the calcium salt and urea solution due to bacterial hydrolysis of urea. In this paper, the effect of intact cell suspension of Bacillus sp. strain VS1, suspension of the washed bacterial cells, and culture liquid without bacterial cells on microbially induced calcite precipitation in sand was studied. The test results showed that adsorption/retention of urease activity on sand treated with washed cells of Bacillus sp. strain VS1 was 5–8 times higher than that treated with culture liquid. The unconfined compressive strength of sand treated with the suspension of washed cells was 1.7 times higher than that treated with culture liquid. This difference could be due to fast inactivation of urease by protease which was present in the culture liquid. The adsorption of bacterial cells on sand pretreated with calcium, aluminum, or ferric salts was 29–37 % higher as compared with that without pretreatment. The permeability of sand varied with the content of precipitated calcium. For bioclogging of sand, the content of precipitated calcium had to be 1.3 % (w/w) or higher. The shear strength of biotreated sand was also dependent on the content of precipitated calcium. To achieve an unconfined compressive strength of 1.5 MPa or higher, the content of precipitated calcium in the treated sand had to be 4.2 % (w/w) or higher. These data can be used as the reference values for geotechnical applications such as bioclogging for reducing the permeability of sand and biocementation for increasing the shear strength of soil.